Regulating labour platforms, the data deficit - Adrian John Hawley (European Journal of Government and Economics, 2018)
It is widely reported that there is a data deficit regarding working conditions in the gig economy. It is known, however, that workers are disadvantaged because they are not classed as employees with the result that they lack work-related entitlements and may not be protected by the social welfare safety net. Nor is this compatible with the social market economy enshrined in the European Union treaties. Two obstacles are that labour law and social policy are mainly a national competence and that platforms are reluctant to share data with regulators. In this paper I take the specific case of offline labour platforms intermediated by app and smart phone such as driving and delivering and look for new pathways between access to data and the shaping of public policy in member states with potentially legal certainty.